1978
DOI: 10.1093/nar/5.11.4399
|View full text |Cite
|
Sign up to set email alerts
|

Spatial configuration of deoxyribotrinucleoside diphosphates in aqueous solution

Abstract: The detailed conformational features and dynamics of the naturally occurring deoxyribotrinucleoside diphosphates d-TpTpT and d-TpTpC have been investigated at 20 degrees C and 80 degrees C in aqueous solution by nuclear magnetic resonance spectroscopy. The observed NMR parameters indicate that the conformational properties of the trimers are very similar to those of the constituent dimers and monomers, i.e., the monomers and dimers conserve their intrinsic conformational features when they become incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…2). The flaps were comprised of different lengths of oligodeoxythymidine in order to minimize secondary structure formation (11). We found that flap cleavage efficiency decreased markedly with increasing flap length, from 80% cleavage with a 20-bp flap to 28% with a 120-bp flap.…”
Section: Resultsmentioning
confidence: 99%
“…2). The flaps were comprised of different lengths of oligodeoxythymidine in order to minimize secondary structure formation (11). We found that flap cleavage efficiency decreased markedly with increasing flap length, from 80% cleavage with a 20-bp flap to 28% with a 120-bp flap.…”
Section: Resultsmentioning
confidence: 99%
“…The H2' and H2" protons of a particular residue are distinguished on the basis of (a) the larger deshielding effect of 3'-phosphorylation at H2", (b) the deshielding effect of 04-alkylation at H2" (0.09 ppm) and comparable shielding effect at H2' (0.07 ppm) observed at the nucleoside level, and (c) coupling constant trends (26,27). The H5' and H5" protons were assigned according to the literature (28).…”
Section: Results and Discussion ' H Nuclear Magnetic Resonance Spectrmentioning
confidence: 99%
“…At 20°C the Np and pN fragments of the three dimers show preferences for gf in the narrow range 6 1 1+-5 and 79 + 2%, respectively. A preference for gf is generally observed in oligomers (27,29,30). Increasing the temperature to 70°C reduces this preference in Np to 52 & 2%, and in pN to 64 -+ 2%.…”
Section: Sugar Conformationmentioning
confidence: 94%
See 1 more Smart Citation
“…No such effects are observed for the pNp fragment of the all-pyrimidine trimers 7 (Table 1) and 21 (33). However, it is surprising that As(H2') for the trimers at 10°C is only 60% of that for the dimers 1 and 4.…”
Section: Chemical Shift Temperature Projiles: Pyrimidine Unitsmentioning
confidence: 92%